Pengaruh Stres Kerja, Kepuasan Kerja, Dan Lingkungan Kerja Terhadap Produktivitas Karyawan PT. Arya Swastika Adhiguna - Setiyawan, Rendy; Khalikussabir, Khalikussabir; Mahardani, Ahmad Subhan (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the influence of job stress, job satisfaction, and work environment on employee productivity at PT. Arya Swastika Adhiguna. The background of this research is based on the importance of professional human resource management, particularly in the construction industry which is characterized by high-risk jobs. The research method employed is a quantitative approach using a saturated sampling technique, involving 30 employees as respondents. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that simultaneously, job stress, job satisfaction, and work environment have a significant effect on employee productivity. Partially, job stress has a significant negative effect, while job satisfaction and work environment have a significant positive effect on productivity. The conclusion of this study suggests that managing job stress effectively, along with improving job satisfaction and a conducive work environment, can enhance employee productivity. Therefore, companies must pay attention to these three aspects in their human resource management strategies to achieve optimal performance. This research provides both theoretical and practical contributions to the development of human resource strategies in the construction sector Keywords: Job Stress, Job Satisfaction, Work Environment, Employee Productivity